Effect of Lupeol on Inducing the Nitric Oxide Production in Macrophages Infected with Leishmania Donovani - Abbas, Talib Fadhil; Ali, Hayder Zuhair (Iraqi Journal of Science, 2025)
Visceral leishmaniasis is a neglected tropical disease on the rise in different regions of Iraq, especially in areas with poor hygiene and among refugee populations. The effectiveness of existing chemotherapy for leishmaniasis is constrained by its high toxicity, cost, and the development of drug resistance. The current research examined various concentrations (ranging from 125 to 1000 μM) of lupeol to evaluate its ability to boost the generation of nitric oxide, which has anti-leishmanial properties, in an ex-vivo macrophage model. Griess assay was used to detect the nitric oxide (NO) production in Leishmania donovani infected U937 cell-line macrophages along 24 and 48 hours post treated. The nitric oxide concentration was significantly increased (P≤0.05) in the treated infected-macrophages after 24 and 48 hours post treated. Furthermore, the infectivity index was calculated for ex vivo amastigote-macrophage infection and the results showed a significant decrease in the percentage of invasion at higher concentrations of Lupeol at all periods of incubation (P≤0.05); whereas, the average of amastigotes per cell in lupeol-treated macrophages increased significantly (P≤0.05) only after 48hours of incubation. The results indicate that lupeol has the potential to enhance anti-leishmanial nitric oxide production by macrophages, enabling them to eliminate intracellular amastigote forms of the parasite. Further details on effect of Lupeol can be studied as a promising anti-leishmanial compound.